Long-Term Changes of Particle Flux in the Canary Basin Between 1991 and 2009 and Comparison to Sediment Trap Records Off Mauritania - Fischer, Gerhard; Neuer, Susanne; Ramondenc, Simon; Müller, Thomas J.; Donner, Barbara; Ruhland, Götz; Ratmeyer, Volker; Meinecke, Gerrit; Nowald, Nico; Klann, Marco; Wefer, Gerold (Frontiers in Earth Science, 2020)
Eastern Boundary Upwelling Ecosystems (EBUEs) are associated with high biological productivity, high fish catch and they highly contribute to marine carbon sequestration. Whether coastal upwelling has intensified or weakened under climate change in the past decades is controversially discussed and different approaches (e.g. time-series of chlorophyll, wind, sea surface temperature, modelling experiments) have been considered. We present a record of almost two decades of particle fluxes (1991-2009) from ca. 600 to 3100 m water depth in the Canary Basin at site ESTOC (European Station for Time series in the Ocean Canary Islands; ca. 29°N, 15°30.W, ca. 3600 m water depth), located in the offshore transition zone of the northern Canary Current-EBUE. We compare these flux records with those measured at a mesotrophic sediment trap site further south off Cape Blanc (Mauretania, ca. 21°N). The deep ocean fluxes at ESTOC in ca. 3 km recorded the evolution of the coastal Cape Ghir filament (30-32°N, 10-12°W) due to lateral advection of particles, whereas the upper water column sediment traps in ca. 1 km reflected the oligotrophic conditions in the overlying waters of ESTOC. We observed an increased emphasis in spring-time fluxes since 2005, associated with a change in particle composition, while satellite chlorophyll biomass did not show this pattern. Due to its northern location in the CC-EBUEs, spring biogenic fluxes at ESTOC provide a better relationship to the forcing of the North Atlantic Oscillation than those recorded further south off Cape Blanc. Off Cape Blanc, deep fluxes showed the best overlap with the deep ESTOC fluxes during the spring season before 2005. On the long-term, both chlorophyll and particle fluxes showed an increasing trend at ESTOC which was not observed further south at the mesotrophic Cape Blanc site. This might indicate that, depending on their location along the NW African margin, coastal upwelling systems react differently to global change.